Group Communication in Rising Students of Singapore Open University POKJAR: Komunikasi Kelompok Pada Mahasiswa Rising Universitas Terbuka POKJAR Singapura - Dewi, Audry Shintya; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2025)
This journal discusses group communication among students of Universitas Terbuka Pokjar Singapore with a focus on the groupthink theory. The purpose of this research is to descriptively explore the influence of group communication on the achievement of shared goals among students and also the handling of each member in facing obstacles from the attitude of the instructor in conducting lectures. The research method used is descriptive research with data collection through observation and structured interviews with several groups of students. Using the Groupthink theory according to Raimond Cattel to achieve results. The research results show that support from each group member is very much needed, as some members face obstacles from the employer that hinder them and require special support and solutions from each member. This finding shows the importance of paying attention to group communication aspects in optimizing the achievement of common goals in the academic environment. The implications of this research provide valuable knowledge or understanding for the development of group communication strategies among students of Universitas Terbuka Pokjar Singapore.